The encyclopedia of weather and climate change : a complete visual guide - Fry, Juliane L. (Juliane Loraine) (University of California Press, 2010)
Go beyond simple definitions to explore where weather comes from and the roles played by oceans and water cycles. Learn about related phenomena such as the shaping of landforms, the creation of biological provinces, and the lasting ramifications of climate change.